Change in the social context of physical activity across adolescence and its association with moderate-to-vigorous intensity physical activity. (May 2022) - Stearns, Jodie A.; Bélanger, Mathieu; O'Loughlin, Jennifer; Brunet, Jennifer
Abstract: We examined whether changes in social context (i.e., frequency with which youth engage in physical activity [PA] alone, with teammates, with friends, with siblings, or with parents/grandparents) is associated with change in moderate-to-vigorous intensity PA (MVPA) across Grades 5–8 and Grades 8–11 (N = 938). Data were self-reported annually. Across Grades 5–8, the frequency of PA in all social contexts declined over time, and changes in the frequency of PA alone, with teammates, with siblings, and in diversity of PA companion types were positively associated with change in MVPA. Across Grades 8–11, the frequency of PA with siblings, friends, and parents/grandparents declined over time, and changes in the frequency of PA alone, with teammates, with friends, with parents/grandparents, and in diversity of PA companion types were positively associated with change in MVPA. PA social contexts vary in how they associate with change in MVPA in youth over time. Highlights: Data were analyzed using piecewise latent growth modeling. Physical activity (PA) declined over time in most social contexts. Change in PA alone or with teammates associated with moderate-to-vigorous PA (MVPA). Associations between change in PA with companions and MVPA varied by school level. Change in diversity of PA companion types associated with change in MVPA.